ALGORITHM FOR SEARCHING THE ATTRACTOR OF GENERAL VIEW DYNAMIC SYSTEM - Vejtsblit, О.Й. (Journal of Information Technologies in Education (ITE), 2010)
In this article the effective algorithm allowing finding the attractor of any dynamic system in view of its irremovable casual fluctuations is represented.